Assessing the Social and Psychological Impacts of Endemic Animal Disease Amongst Farmers - Crimes, Delyth; Enticott, Gareth (Frontiers in Veterinary Science, 2019)
Outbreaks of exotic animal disease, such as Foot and Mouth Disease (FMD) are associated with social and psychological impacts amongst farmers. Whilst claims of similar impacts for endemic diseases have been made, there is little empirical evidence to justify these assertions. This paper provides a descriptive analysis of the social and psychological impacts of bovine Tuberculosis (bTB) in Wales. Specifically, the paper focuses on farmers subjective well-being and presenteeism – their propensity to work suboptimally when suffering mental health problems. Results from qualitative interviews reveal how farmers derive satisfaction from their work and their emotional connection to animals, whilst the weather and red tape are most likely to affect their quality of life. Data from a postal survey (n=582) using three measures of SWB, however, finds mixed evidence that animal disease is associated with farmer well-being. For all farmers surveyed, there were no significant differences in well-being between farms with and without bTB. For those farms in areas with high bTB prevalence, two of the three measures of SWB showed lower levels of well-being for farmers with a history of bTB (p<0.05). In conclusion, the paper discusses the policy and methodological implications for future studies of farmer well-being and animal disease.